Cardioverter defibrillator implantation without induction of ventricular fibrillation: a single-blind, non-inferiority, randomised controlled trial (SIMPLE). Issue 9970 (28th February 2015) - Healey, Jeff S; Hohnloser, Stefan H; Glikson, Michael; Neuzner, Jorg; Mabo, Phillipe; Vinolas, Xavier; Kautzner, Josef; O'Hara, Gilles; VanErven, Lieselot; Gadler, Fredrik; Pogue, Janice; Appl, Ursula; et al.
Summary: Background: Defibrillation testing by induction and termination of ventricular fibrillation is widely done at the time of implantation of implantable cardioverter defibrillators (ICDs). We aimed to compare the efficacy and safety of ICD implantation without defibrillation testing versus the standard of ICD implantation with defibrillation testing. Methods: In this single-blind, randomised, multicentre, non-inferiority trial (Shockless IMPLant Evaluation [SIMPLE]), we recruited patients aged older than 18 years receiving their first ICD for standard indications at 85 hospitals in 18 countries worldwide. Exclusion criteria included pregnancy, awaiting transplantation, particpation in another randomised trial, unavailability for follow-up, or if it was expected that the ICD would have to be implanted on the right-hand side of the chest. Patients undergoing initial implantation of a Boston Scientific ICD were randomly assigned (1:1) using a computer-generated sequence to have either defibrillation testing (testing group) or not (no-testing group). We used random block sizes to conceal treatment allocation from the patients, and randomisation was stratified by clinical centre. Our primary efficacy analysis tested the intention-to-treat population for non-inferiority of no-testing versus testing by use of a composite outcome of arrhythmic death or failed appropriate shock (ie, a shock that did not terminate a spontaneous episode of ventricular tachycardia or fibrillation). The non-inferiority margin was a hazard ratio (HR) of 1·5 calculated from a proportional hazards model with no-testing versus testing as the only covariate; if the upper bound of the 95% CI was less than 1·5, we concluded that ICD insertion without testing was non-inferior to ICD with testing. We examined safety with two, 30 day, adverse event outcome clusters. The trial is registered withClinicalTrials.gov, numberNCT00800384 . Findings: Between Jan 13, 2009, and April 4, 2011, of 2500 eligible patients, 1253 were randomly assigned to defibrillation testing and 1247 to no-testing, and followed up for a mean of 3·1 years (SD 1·0). The primary outcome of arrhythmic death or failed appropriate shock occurred in fewer patients (90 [7% per year]) in the no-testing group than patients who did receive it (104 [8% per year]; HR 0·86, 95% CI 0·65–1·14; pnon-inferiority <0·0001). The first safety composite outcome occurred in 69 (5·6%) of 1236 patients with no-testing and in 81 (6·5%) of 1242 patients with defibrillation testing, p=0·33. The second, pre-specified safety composite outcome, which included only events most likely to be directly caused by testing, occurred in 3·2% of patients with no-testing and in 4·5% with defibrillation testing, p=0·08. Heart failure needing intravenous treatment with inotropes or diuretics was the most common adverse event (in 20 [2%] of 1236 patients in the no-testing group vs 28 [2%] of 1242 patients in the testing group, p=0·25). Interpretation: Routine defibrillation testing at the time of ICD implantation is generally well tolerated, but does not improve shock efficacy or reduce arrhythmic death. Funding: Boston Scientific and the Heart and Stroke Foundation (Ontario Provincial office).